GLAUCOMA: SECRETS OF SILENT THIEF OF VISION – A REVIEW - Opeyemi, Oyeniran Taiwo (Universal Journal of Pharmaceutical Research, 2017)
Glaucoma has been highlighted as a priority eye disease by the World Health Organization’s global initiative to eliminate avoidable blindness by the year 2020. Glaucoma is defined as an optic neuropathy, characterized for loss of visual field and injury of the optic nerve. However the mechanism leading to the disease is still unclear. Factors that are responsible for it include glutamate-induced neurotoxicity, nitric oxide based damage, disruption of neurotrophic factor transport and immune-induced neuro destruction. At present treatment options primarily aim at decreasing intra-ocular pressure (IOP) by utilizing pharmacological agents, laser therapy and surgery. Gaining a better understanding of the pathogenesis can aid in the development of new treatment options and, perhaps, even a cure for glaucoma. Since there is no cure for Glaucoma, early detection and treatment can slow or prevent further vision lossThis article discusses the pathophysiology of glaucoma, its detection, diagnosis monitoring and treatment. Peer Review History: Received 6 April 2017; Revised 9 May; Accepted 30 June; Available online 15 July 2017 Academic Editor: Ahmad Najib , Universitas Muslim Indonesia, Indonesia, ahmad.najib@umi.ac.id Reviewer(s) detail: Dr. Emmanuel O. Olorunsola , Department of Pharmaceutics & Pharmaceutical Technology, University of Uyo, Nigeria, olorunsolaeo@yahoo.com Dr. Heba M. Abd El-Azim , Damanhour University, Egypt, h_m_abdelazim@hotmail.com